Ibrutinib Promotes Atrial Fibrillation by Disrupting A-Kinase Anchoring Protein 1-Mediated Mitochondrial Quality Surveillance in Cardiomyocytes - Yukun Li; Xinmeng Liu; Rong Lin; Xiaodong Peng; Xuesi Wang; Fanchao Meng; Shuqi Jin; Wenhe Lv; Xiaoying Liu; Zhuohang Du; Songnan Wen; Rong Bai; et al. (Research)
Background: Ibrutinib, a potent Bruton’s tyrosine kinase inhibitor with marked efficacy against hematological malignancies, is associated with the heightened risk of atrial fibrillation (AF). Although ibrutinib-induced AF is linked to enhanced oxidative stress, the underlying mechanisms remain unclear. Objective: This research aimed to explore the molecular mechanism and regulatory target in ibrutinib-induced AF. Methods: We performed in vivo electrophysiology studies using ibrutinib-treated mice, and then employed proteomic and single-cell transcriptomic analyses to identify the underlying targets and mechanisms. The effects of A-kinase anchoring protein 1 (AKAP1) depletion on mitochondrial quality surveillance (MQS) were evaluated using both in vivo and ex vivo AKAP1 overexpression models. Results: Atrial AKAP1 expression was significantly reduced in ibrutinib-treated mice, leading to inducible AF, atrial fibrosis, and mitochondrial fragmentation. These pathological changes were effectively mitigated in an overexpression model of ibrutinib-treated mice injected with an adeno-associated virus carrying Akap1. In ibrutinib-treated atrial myocytes, AKAP1 down-regulation promoted dynamin-related protein 1 (DRP1) translocation into mitochondria by facilitating DRP1 dephosphorylation at Ser637, thereby mediating excessive mitochondrial fission. Impaired MQS was also suggested by defective mitochondrial respiration, mitochondrial metabolic reprogramming, and suppressed mitochondrial biogenesis, accompanied by excessive oxidative stress and inflammatory activation. The ibrutinib-mediated MQS disturbance can be markedly improved with the inducible expression of the AKAP1 lentiviral system. Conclusions: Our findings emphasize the key role of AKAP1-mediated MQS disruption in ibrutinib-induced AF, which explains the previously observed reactive oxygen species overproduction. Hence, AKAP1 activation can be employed to prevent and treat ibrutinib-induced AF.